My Surface - Cheshire, Jim.; Safari eBooks (Indianapolis, Ind. : Que, 2012)
The Surface is the first tablet computer released by Microsoft.
Description based on print version record.
Includes index.
Keywords: Tablet computers; Surface (Computer); Electronic books